Optimalisasi Kemampuan Pertolongan Pertama Dislokasi Pada Cedera Ringan dengan Metode Demonstrasi dan Video Animasi pada Remaja - Sari, Melani Kartika (STIKES dan AKZI Karya Husada Kediri, 2025)
Dislocation is a common minor injury among adolescents, particularly those resulting from physical activity and sports. Inappropriate first aid treatment can lead to complications and alleviate the injury. However, adolescents' ability to perform first aid for dislocations remains low. Therefore, effective educational methods, such as compression and animated videos, are needed to improve these skills. This study used a pre-experimental design with a one-group pretest-posttest approach. Thirty adolescents were selected using a total sampling technique. Data analysis was performed using the Wilcoxon test to determine differences in skills before and after the intervention. The statistical test showed a significance value of p = 0.00 (p < 0.05), indicating a significant difference between skills before and after the intervention. The compression method and animated videos proved effective in improving adolescents' first aid skills for dislocations. The combination of visualization and hands-on practice helped respondents understand the material more optimally. This method can be recommended as a health education strategy to improve adolescents' preparedness in handling minor injuries.